Gists gastrointestinal stromal tumors - de Lutio di Castelguidone, Elisabetta (Springer)
This book aims to provide a complete overview of the diagnosis and treatment of gastrointestinal stromal tumors (GISTs). It has been conceived to be both a detailed guide for clinical practice and an updated reference for all those involved in the evaluation of GISTs imaging. The publication provides comprehensive descriptions of the full range of common imaging and nonimaging techniques used in the diagnosis and followup of GISTs. Techniques reviewed include: · Conventional radiography · Endoscopy and endoscopic ultrasound · Conventional, color-Doppler and contrast-enhanced ultrasound · Computed tomography · Magnetic resonance imaging, and · Contrast-enhanced PET/CT imaging Both medical and surgical treatment strategies are also fully reviewed. Finally, the book concludes with a chapter that aims to stimulate widespread interest in the formation of new GISTs Units. Written by experts in the field, the book is enriched throughout by numerous black-and-white and color images, making it an invaluable source of information as well as an indispensable guide to interpreting images for radiologists, gastroenterologists, pathologists, oncologists and surgeons.  .